2005
DOI: 10.1080/14992020500189062
|View full text |Cite
|
Sign up to set email alerts
|

Variation of young normal-hearing thresholds measured using different audiometric earphones: Implications for the acoustic coupler and the ear simulator

Abstract: This paper questions the necessity for two calibration devices to measure the acoustic output from different types of audiometric earphones. International standards give the audiometric zero for TDH39 earphones on the IEC 60318-3 acoustic coupler; the IEC 60318-1 ear simulator is intended for other supra-aural earphone types. If hearing threshold samples from young, healthy ears were found to be more variable using TDH39 earphones, then that earphone and its coupler might be taken out of service. The audiologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 13 publications
1
7
1
Order By: Relevance
“…These thresholds are elevated as compared with a study on individuals aged 16 to 27 years old without cleft with mean thresholds of 2 dBHL and 4 dBHL at 6,000 and 8,000 Hz (39). In the present study, the elevated mean thresholds in the high frequencies were exhibited from 10 years of age.…”
Section: Discussioncontrasting
confidence: 53%
“…These thresholds are elevated as compared with a study on individuals aged 16 to 27 years old without cleft with mean thresholds of 2 dBHL and 4 dBHL at 6,000 and 8,000 Hz (39). In the present study, the elevated mean thresholds in the high frequencies were exhibited from 10 years of age.…”
Section: Discussioncontrasting
confidence: 53%
“…Most participants exhibiting a notch audiogram using TDH-50P headphones revealed a flat audiometric configuration when ER-3A receivers were used to measure hearing thresholds. The results of the study are in agreement with a previously published report showing that RESPL values of supra-aural and insert receivers were substantially different (Valente et al 59 ), which might influence hearing threshold measurement at high frequencies (McBride and Williams 31 ; Lawton 22 ; Schlauch and Carney 47 ; Schlauch and Carney 48 ). Therefore, supra-aural receivers should not be used to investigate NIHL in young adults, especially when less restrictive notch identification criteria are used.…”
Section: Discussionsupporting
confidence: 91%
“…Recent analyses of the NHANES 1999 -2004 dataset showed that diabetes and heavy smoking were associated with increased hearing loss (Agrawal et al 2008;Bainbridge et al 2008). This effect has been seen in other studies (Arlinger 1991;Lutman & Davis 1994) and has been attributed to an error in the reference value for audiometric zero when calibrating TDH-39 headphones on an NBS-9A (6 cm 3 ) acoustic coupler (Robinson et al 1981;Lutman & Qasem 1998;Lawton 2005). Unquestionably, our population smokes far less today than in 1962.…”
Section: Discussionmentioning
confidence: 67%